Sharing of tacit knowledge in volunteer Portuguese firefighters – paths to diagnosis - Oliveira, Márcio (2021)
Purpose - focusing on the study of tacit knowledge sharing in nonprofit organizations (NPOs) in Portugal and taking as a case study the Portuguese voluntary firefighters, we set as objectives, identify the most relevant factors for sharing tacit knowledge and identify the types of barriers most prevalent to such sharing in these organizations. Design / methodology / approach - a literature review on tacit knowledge sharing allowed the identification of indicators and barriers to the sharing of this knowledge. This was followed by a mixed methodology that combines qualitative and quantitative techniques through questionnaires and interviews, whose treatment allowed to determine the indicators that influence each of these factors and which types of barriers. Findings - Three factors have been identified that lead to the sharing of tacit knowledge within these organizations: organizational culture, individual characteristics, and organizational structure. Four typologies of barriers were identified: communicational, technological, personal and resource or infrastructure. Research limitations / implications - The present research focuses exclusively on the sharing of tacit knowledge, not considering other forms of knowledge. As a case study, although with heterogeneous organizations, the same cannot be replicated to different realities. Originality / Value - Studies in this area, targeting NPOs are scarce, as opposed to what is happening in the private and public sectors. The option of a case study of organizations such as the Portuguese fire brigades (FBs), unique in their action and identity, accompanies the need increasingly recognized by society, in enabling these organizations of competencies for the best possible performance, in the face of tragic events that have occurred in recent years in Portugal.